Squares and Pairs

Algebra Level 2

Take a pair of numbers that are an even distance apart, then multiply them together.

2 × 4 = 8 20 × 36 = 720 519 × 93 = 48267 \begin{aligned} 2\times 4&=8 \\ 20\times 36&=720 \\ 519\times 93&=48267 \end{aligned}

With these three examples, we see a peculiar pattern emerge.

8 + 1 2 = 3 2 720 + 8 2 = 2 8 2 48267 + 21 3 2 = 30 6 2 \begin{aligned} 8+1^2 & = 3^2 \\ 720 + 8^2 & = 28^2\\ 48267 + 213^2 & = 306^2 \end{aligned}

Each of these products are some square number less than another square number!
Is this the case for every pair of numbers with even distance?

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Braden Dean
Jun 4, 2018

Let a a and b b be any pair of integers an even distance apart, with a < b a<b , and a b = z a \cdot b = z
Let x x be the arithmetic mean of these two numbers. We know that x x must be an integer since a a and b b are an even distance apart.
Let y = x a = x b y=|x-a|=|x-b|
Therefore, a = x y a=x-y , and b = x + y b=x+y
Plugging these into the first equation, we get ( x y ) ( x + y ) = z (x-y)(x+y)=z
This is a difference of squares; we then know that x 2 y 2 = z x^2-y^2=z
Finally, that means z + y 2 = x 2 z+y^2=x^2 , making the product of any two integers an even distance apart added to their distance to their arithmetic mean squared is always equal to their arithmetic mean squared.
Therefore, the answer must be Yes .

Eric Schneider
Jun 4, 2018

Let a a and n n be arbitrary integers. Then our pair of numbers will be a a and a + 2 n a+2n .
The product of these integers are a ( a + 2 n ) = a 2 + 2 a n a(a+2n)=a^2+2an .
By adding n 2 n^2 , we find that we have a ( a + 2 n ) + n 2 = a 2 + 2 a n + n 2 = ( a + n ) 2 a(a+2n)+n^2=a^2+2an+n^2=(a+n)^2 .
So for any two integers a distance 2 n 2n apart, we know that adding n 2 n^2 will result in a square number.

There is an alternative and more concise proof, but that will be left as an exercise to the reader. :-)

Good question with excellent answer

Ram Mohith - 3 years ago
Jeffrey Robles
Jun 6, 2018

Denote the two numbers as k k and k + 2 x k + 2x . Their product is thus equal to k ( k + 2 x ) k\cdot(k+2x) . Note that

k ( k + 2 x ) = ( k + x x ) ( k + x + x ) = ( k + x ) 2 x 2 k\cdot(k+2x)=(k+x-x)(k+x+x)=(k+x)^2 - x^2

Clearly, the product k ( k + 2 x ) k\cdot(k+2x) can be written as a difference of two squares. Equivalently, as phrased in the problem, each product is some square number less than another square number .

For verification, here are the given items in the problem: 2 4 = 2 ( 2 + 2 1 ) = ( 2 + 1 1 ) ( 2 + 1 + 1 ) = ( 2 + 1 ) 2 1 2 = 3 2 1 2 = 8 2\cdot4=2\cdot(2 + 2\cdot 1) = (2 + 1 - 1)(2 + 1 + 1) = (2+1)^2 - 1^2 = 3^2 - 1^2 = 8 20 36 = 20 ( 20 + 2 8 ) = ( 20 + 8 8 ) ( 20 + 8 + 8 ) = ( 20 + 8 ) 2 8 2 = 2 8 2 8 2 = 720 20\cdot36=20\cdot(20 + 2\cdot 8) = (20 + 8 - 8)(20 + 8 + 8) = (20+8)^2 - 8^2 = 28^2 - 8^2 = 720 519 93 = 93 ( 93 + 2 213 ) = ( 93 + 213 213 ) ( 93 + 213 + 213 ) = ( 93 + 213 ) 2 21 3 2 = 30 6 2 21 3 2 = 48 , 267 519\cdot93=93\cdot(93 + 2\cdot 213) = (93 + 213 - 213)(93 + 213 + 213) = (93+213)^2 - 213^2 = 306^2 - 213^2 = 48,267

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...